2018
DOI: 10.5194/acp-18-14017-2018
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and physical characteristics of aerosol at a remote free troposphere site: implications for atmospheric aging

Abstract: Aerosol properties are transformed by atmospheric processes during long-range transport and play a key role in the Earth's radiative balance. To understand the molecular and physical characteristics of free tropospheric aerosol, we studied samples collected at the Pico Mountain Observatory in the North Atlantic. The observatory is located in the marine free troposphere at 2225 m above sea level, on Pico Island in the Azores archipelago. The site is ideal for the study of long-range-transported free tropospheri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(105 citation statements)
references
References 107 publications
8
95
2
Order By: Relevance
“…Understanding the role of clouds and humidity in impacting SOA formation and evolution has received scarce attention over the WNAO, in contrast to other regions such as the northeastern Pacific Ocean (Sorooshian et al, ; Sorooshian et al, ). Schum et al () showed that the oxygen‐to‐carbon (O:C) ratio for wildfire‐influenced aerosols (~0.45–0.48) transported over 7–10 days in the free troposphere to the PICO Mountain Observatory in the North Atlantic was lower compared to that of North American outflow aerosols transported mainly through the MBL over only three days (~0.57). While the O:C ratio difference was attributed to the free tropospheric particles being more viscous and thus less vulnerable to oxidation than the MBL aerosols, it is worth considering in future model‐measurement studies how enhanced humidity and cloudiness in the WNAO MBL could enhance the O:C ratio via aqueous oxidation pathways (Ervens et al, ; Ervens et al, ).…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
“…Understanding the role of clouds and humidity in impacting SOA formation and evolution has received scarce attention over the WNAO, in contrast to other regions such as the northeastern Pacific Ocean (Sorooshian et al, ; Sorooshian et al, ). Schum et al () showed that the oxygen‐to‐carbon (O:C) ratio for wildfire‐influenced aerosols (~0.45–0.48) transported over 7–10 days in the free troposphere to the PICO Mountain Observatory in the North Atlantic was lower compared to that of North American outflow aerosols transported mainly through the MBL over only three days (~0.57). While the O:C ratio difference was attributed to the free tropospheric particles being more viscous and thus less vulnerable to oxidation than the MBL aerosols, it is worth considering in future model‐measurement studies how enhanced humidity and cloudiness in the WNAO MBL could enhance the O:C ratio via aqueous oxidation pathways (Ervens et al, ; Ervens et al, ).…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
“…The relatively large variability among the miscibility limits in terms of O : C ratio emphasizes the importance of distinguishing among different types of oxygen-bearing functional groups. In the case of ambient and laboratory-generated aerosol mixtures containing inorganic salts, the transition from LLPS to completely miscible (at any composition) spans a O : C ratio range from 0.4 to 0.8 based on experimental data (Song et al, 2012;You et al, 2014;You and Bertram, 2015). That O : C range is comparable to the difference between a hydroperoxide molecule with a molar mass of 100 g mol −1 vs. 400 g mol −1 .…”
Section: Molecular Functionality Translationmentioning
confidence: 99%
“…The residual OM was calculated by subtracting the weighted sum of the major inorganic chemical constituents and elemental carbon from PM 2.5 mass for each SEARCH sample using the equation described by Hand et al (2012). A particle water correction was made (Dabek-Zlotorzynska et al, 2011;Simon et al, 2011). Metrics used between measured and reference OM or OC were coefficient of determination R 2 , bias-corrected error (also known as the median absolute deviation, as previously described by Weakley et al, 2016), and orthogonal least-squares regression slope.…”
Section: Model Evaluation: Interpretation Of Model Predictors and Commentioning
confidence: 99%
“…Other methods with involved chemical analyses of discrete filter samples have been used to estimate OM concentration. These include multiple linear regression of aerosol constituents using various analytical techniques (Hand et al, 2019;Malm and Hand, 2007;Simon et al, 2011), extrapolation from gas chromatography-mass spectrometry of extracts (Turpin and Lim, 2001), infrared absorption spectrometry of extracts (Polidori et al, 2008), or thermal-optical and gravimetric analyses of extracts (El-Zanan et al, 2009). However, each of these methods is subject to specific limitations.…”
mentioning
confidence: 99%